せん断応力による血液凝固反応抑制の定量評価と反応メカニズム - 西田, 正浩; 小阪, 亮; 丸山, 修; 迫田, 大輔; 川上, 滉貴; 山根, 隆志 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
It is important to inhibit thrombus formation in a blood pump applicable to severe heart failure patient. Blood coagulation reaction are different depend not only on the blood coagulability of the patients but also on the degree of shear stress. However, it is not clear the relationship between the degree of shear stress and the amount of thrombus. The, we utilized a rheometer which is able to load homogeneous shear stress to the test blood, and measured blood coagulation time and the amount of thrombus for bovine blood. As a result, blood coagulation reaction time became long with the increase in shear stress, but the amount of thrombus was almost the same at same shear stress even in different ACT test blood. We also obtained that the inhibition mechanism of blood coagulation reaction under shear stress was related to the blood coagulation factor V for porcine and human blood.